KINERJA KARYAWAN ROOM ATTENDANT DI HOTEL MUTIARA MERDEKA PEKANBARU - Ataya Hanna Nursillam S; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The existence of this research is intended to be able to find out how the performance of room attendant employees on the satisfaction of guests staying at Mutiara Merdeka Hotel Pekanbaru. In this research, the writer uses quantitative descriptive method. Questionnaires were distributed by 100 respondents, while the technique of data collection for this study used observations, questionnaires and documentation. The results of this study indicate that respondents assess the performance of room attendant employees at Mutiara Merdeka Hotel Pekanbaru to get satisfied results. It can be seen from the average results of each service indicator variable to guests (52.05%), cleanliness indicator (52.6%), facilities indicator (53.4%), expectation conformity indicator (52.6%), indicator of interest in revisiting (52.06%) and indicator of willingness to recommend (51.2%). It can be concluded that the performance of room attendants to guests is quite good. Thus the performance of the room attendant employees provided by Mutiara Merdeka Hotel Pekanbaru so that it can be further improved. Keywords: employee performance, room attendant, hotel